Virome of neotropical Sabethes mosquitoes reveals two novel viruses in the Spiciviridae family - Endrya do Socorro Foro Ramos; Lilian de Oliveira Guimaraes; Geovani de Oliveira Ribeiro; Marcos Anicete Santos; Ramendra Pati Pandey; Simone Luchetta Reginato; Juliana Telles-de-Deus; Eduardo Sterlino Bergo; Luis Filipe Mucci; Vera Lucia Fonseca de Camargo-Neves; Antonio Charlys da Costa; Elcio Leal; et al. (Virus Genes, 2026)
The family Spiciviridae , belonging to the order Ghabrivirales , is currently composed of only one officially recognized genus, Spicivirus . However, metagenomic studies have revealed an increasing diversity of related viruses, suggesting that the current classification may underestimate their evolutionary complexity. In this context, the aim of the present study was to detect and characterize new viruses related to the Spiciviridae in the family Culicidae mosquitoes. A total of nineteen mosquito pools were sequenced and analyzed using metagenomic approaches and bioinformatics tools. Among these, two novel viruses were identified in four pools (S4, S11, S18, and S19), provisionally named Sabethes virus 1 (SV1) and Sabethes virus 2 (SV2). Phylogenetic inference revealed clades with strong statistical support and genetic divergences greater than 20% in the RNA-dependent RNA polymerase (RdRp) protein. These findings contribute to a detailed analysis of the genomic diversity associated with Spiciviridae . Although Spicivirus is currently the only genus officially recognized, our results suggest the presence of viruses that may represent new taxonomic groupings not yet described by the ICTV.

Wyeomyia confusa Lispivirus (WcLispV-SP): a novel neotropical mosquito virus in the Lispiviridae family - Lilian de Oliveira Guimarães; Roseane da Silva Couto; Simone Luchetta Reginato; Luis Filipe Mucci; Ramendra Pati Pandey; Vera Lucia Fonseca de Camargo-Neves; Antonio Charlys da Costa; Karin Kirchgatter; Elcio Leal (Archives of Virology, 2026)
Metatranscriptomic analysis of Wyeomyia confusa mosquitoes collected in the Atlantic Forest (Pindamonhangaba, São Paulo, Brazil) led to the identification of a previously uncharacterized virus, designated Wyeomyia confusa Lispivirus (WcLispV-SP), classified within the family Lispiviridae , genus Canmovirus . The viral genome consists of a negative-sense single-stranded RNA (ssRNA−) of 12,698 nucleotides, encoding six open reading frames (ORFs): nucleoprotein (N), two hypothetical proteins (HP/1 and HP/2), glycoprotein (G), ORFan protein, and RNA-dependent RNA polymerase (RdRp-L). Phylogenetic analysis supports the classification of WcLispV-SP as a distinct species within the genus Canmovirus . Structural analysis of the RdRp revealed conserved domains and catalytic motifs characteristic of members of the order Mononegavirales , supporting its functional integrity. These findings expand the known diversity of the Lispiviridae family and highlight the utility of metagenomic approaches for the discovery and characterization of RNA viruses associated with Neotropical sylvatic mosquitoes.

Power- and biomass-to-liquid processes with fuel-assisted solid oxide electrolysis cells and water gas shift-adjusted systems: A techno-economic analysis - Samuel M. Krämer; Anders S. Nielsen; Simon Maier; Simone Mucci; Magne Hillestad; Odne S. Burheim (Fuel, 2025)

Cyanobacteria dominance drives zooplankton functional dispersion - Iollanda I. P. Josué; Simone J. Cardoso; Marcela Miranda; Maíra Mucci; Kemal Ali Ger; Fabio Roland; Marcelo Manzi Marinho (Hydrobiologia, 2019)